Effects of corporate governance on the public sector: the case of portuguese municipalities - Da Costa Marques, Maria da Conceição (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this article we will characterize public governance in the municipal area, tracing a perspective of its evolution in Portugal. Corporate governance has deserved increasing attention to this part for some years now, incorporating a set of rules and procedures that aim to optimize the performance of an organization, with observance of principles such as transparency and accountability. Public policies and public administration in general are increasingly influenced by principles and procedures specific to the private sector, with new governance being an administration that is closer to the market. It is concluded that public sector governance currently tends to replace hierarchical and bureaucratic approaches for a more transparent administration.